Scholarly Research in Food Security: A Bibliometric Analysis of Global Food Security. Issue 1 (2nd January 2023) - Ohlan, Ramphul; Ohlan, Anshu
ABSTRACT: This article reviews the publication trends from a top-tier journal covering diverse and interdisciplinary topics related to critical food security research, challenges, and questions. We investigate the bibliometric characteristics of the intellectual structure of Global Food Security: Agriculture, Policy, Economics and Environment ( GFS ), a journal comprised of 311 scholarly documents published between 2012 and 2019. Various datasets are analyzed using standard bibliometric tools, including g-index, m-index, burst detection, and network analysis. The findings of the study indicate that GFS has exhibited promising growth. The number of publications published in GFS and their influence have seen a clearly rising trend year-by-year with contributors from across the globe. The analysis shows that GFS is well connected with other top-tier peer journals on the same subject. Our findings provide several useful insights into the research published in this premier journal about food security. We suggest that there is a need for special emphasis on studies dealing with ethical issues in social decisions on nutrition security as well as research addressing the implications of the globalization of trade in seafood for its access to low-income people.